SISTEM PENDUKUNG KEPUTUSAN DALAM KELAYAKAN PENGAJUAN KREDIT KENDARAAN BERMOTOR DI PERUSAHAAN X MENGGUNAKAN METODE NAÏVE BAYES - Hansen Kurnia, Ricky; Arisandi, Desi; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The purpose of this research is to analyze and design a program that can assist decision making in the process of accepting a motor vehicle loan application in accordance with the given criteria so as to produce a prediction of the value of opportunities in the feasibility of granting motor vehicle loans and minimize human errors that occur in the process Credit Application data analysis. The method used in this research is one of the classification methods, is the Naive Bayes algorithm menthod. The results of the research that has been carried out are applications that are designed to calculate the probability value of the data criteria that have been entered, so that a decision suggestion can be obtained whether the data can be accepted or rejected, from research conducted the more training data provided, the more accurate the value will be. generated probabilities, and the designed application is executed through the Microsoft SQL Server Management Studio (SSMS). From the results of the experiments that have been carried out, it can be seen that the program can provide probability values ​​according to the Naive Bayes method according to the criteria data provided.